Social imaginary and youth participation: realities from the Corregimiento of El Plateado, Municipality of Algeria Cauca - Arboleda Suarez, Denis Antonio (2018)
The following document is part of the results of a research work entitled ‘’ Identities, life projects and community participation of young people in the Corregimiento of El Plateado, Municipality of Algeria Cauca -Colombia ‘’ conducted as a Master’s Thesis in Community Development Sustainable of the National University of Costa Rica, an exercise in which a characterization of youth and youth is carried out and an attempt is made to understand the meanings, obstacles and identify spaces in which young people build their life projects, as well as their forms and participation mechanisms; trying to make visible their capacity for collective action from some local scenarios such as Juventud Rebelde, the Community Action Boards, social organizations such as ASCAMTA, CNA, or actions from the young students; but at the same time, revealing limitations that hinder their real participation from the absence of a defined local identity, persecution of social leaders, little visibility of youth processes, predominance of an adult-centered culture, absence of clear support actions in government spaces local, among others. The document revolves around conceptual aspects related to the construction of collective social imaginary and youth participation, to then present meanings that are woven in some local spaces in which the subjects have an important collective action. In turn, the main obstacles that prevent or limit the development of a more determined task in collective spaces are identified and four scenarios are described from which young people are building that political subject that seeks to vindicate and make visible their capacity for organization.